2013
DOI: 10.1371/journal.pone.0073705
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Analysis of Tooth Agenesis Identifies Novel Mutations in Six Genes and Suggests Significant Role for WNT and EDA Signaling and Allele Combinations

Abstract: Failure to develop complete dentition, tooth agenesis, is a common developmental anomaly manifested most often as isolated but also as associated with many developmental syndromes. It typically affects third molars or one or few other permanent teeth but severe agenesis is also relatively prevalent. Here we report mutational analyses of seven candidate genes in a cohort of 127 probands with non-syndromic tooth agenesis. 82 lacked more than five permanent teeth excluding third molars, called as oligodontia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 48 publications
(97 reference statements)
8
103
0
3
Order By: Relevance
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…Since previous studies involving large numbers of subjects have found that the incidence of phenotypes attributable to PAX9 or MSX1 mutation is in the range of several percent [31,35], this was not unexpected. Those studies found a surprisingly high frequency of WNT10A mutation in patients with tooth agenesis.…”
Section: Discussionmentioning
confidence: 81%
“…(A) Locations of P20L and previously reported missense variants are shown with arrows above and below the PAX9 diagram, respectively [12,2531]. Reported pathogenic variants with nonsense mutations or frameshifts are omitted.…”
Section: Resultsmentioning
confidence: 99%
“…The referral of the patient to a medical evaluation confirmed the diagnosis also based on the clinical findings, corroborating with authors who point out an essentially clinical diagnosis for ED 4,6,11 . Genetic mapping may also be used in order to identify the genes involved and the accurate location of the mutation, a piece of information of utmost importance in order to provide genetic counseling and also anticipate some medical care 25 . Genetic counseling contraindicates consanguineous marriages in order to prevent such X-linked disorders.…”
Section: Discussionmentioning
confidence: 99%
“…At clinical and radiographic examination, no missing teeth were found. The mother also presented few facial features, but the dental involvement was remarkable with 11,12,16,17,18,21,22,25,26,28,45,46,47,48,35, 36, 37, 38 missing teeth. The mother reported in the anamnesis that in adolescence she also had several missing teeth, which suggests that she also presented EDH.…”
Section: Case Reportmentioning
confidence: 99%